2005
DOI: 10.1007/s11249-005-5093-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation behavior of zinc dialkyldithiophosphate in presence of catalyst and detergents in neutral oil

Abstract: Thermal decomposition of zinc dialkyldithiophosphate (ZDDP) is examined in presence of a noble catalyst iron fluoride (FeF 3 ), using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The influence of heating rate, isothermal holding period and catalyst concentration was verified. The role of FeF 3 on ZDDP decomposition mechanism was analyzed using 31 P-NMR. This study also focused on the effect of FeF 3 on ZDDP decomposition in combination with detergents (Ca-sulfonate, Mg-sulfonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The series of peaks at *82-83 and *43 ppm are found to be stronger in intensity in presence of FeF 3 than when ZDDP is baked alone indicating that the decomposition of ZDDP is more rapid in presence of FeF 3 . Earlier DSC studies have shown that the decomposition of ZDDP is accelerated in presence of FeF 3 by at least 10-15% [9]. Compounds of type (RO) 2 P(S)O -(*46 ppm) are not formed here unlike in case of baked ZDDP; however, the other small impurity peaks still remain unchanged.…”
Section: Nmr Analysismentioning
confidence: 80%
See 3 more Smart Citations
“…The series of peaks at *82-83 and *43 ppm are found to be stronger in intensity in presence of FeF 3 than when ZDDP is baked alone indicating that the decomposition of ZDDP is more rapid in presence of FeF 3 . Earlier DSC studies have shown that the decomposition of ZDDP is accelerated in presence of FeF 3 by at least 10-15% [9]. Compounds of type (RO) 2 P(S)O -(*46 ppm) are not formed here unlike in case of baked ZDDP; however, the other small impurity peaks still remain unchanged.…”
Section: Nmr Analysismentioning
confidence: 80%
“…The temperatures reached in an engine are usually in the range of 120-200°C. In this study, the DSC data indicated that both in the case of ZDDP as well as in a mixture of ZDDP and FeF 3 , the decomposition commences at a temperature between 160 and 170°C at heating rates of 0.5°C/min [9]. A temperature of 150°C was chosen for all the degradation experiments.…”
Section: Thermal Decomposition Experimentsmentioning
confidence: 93%
See 2 more Smart Citations
“…It can be seen that DBBM begins to decompose around 150 C, which is similar to ZDDP. 23 It has been reported that the lower the decomposition temperature, the higher the reactivity of the additive to react with a metal surface to form a protective film. From this point of view, it can be considered that the synthesized additive is suitable for using as AW additive.…”
Section: Resultsmentioning
confidence: 99%